What it means to be online for people with disabilities : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Psychology at Massey University, Palmerston North, New Zealand - Bowker, Natilene Irain (Massey University. School of Psychology, 2003)
People with disabilities have traditionally occupied stigmatised identities due to less conventional ways of operating in daily life. The online medium with its absence of visible identity markers, which have typically determined how a person is read offline, combined with the constructive potential embedded within a largely textual medium, potentially, bring together greater control and flexibility in identity construction. The online medium, therefore, may offer social benefits to people with disabilities that are not available in other contexts. This research discursively explores what kinds of experiences are available for people with disabilities online. It argues that the online medium offers alternative subjectivities for positioning people with disabilities in the social world. Discursive findings, however, also show that operating online within a disabled identity creates marginalised experiences.Discourse analysis, underpinned by a social constructionist philosophy, which emphasises the constructive nature of language in creating experience, is utilised as a methodology for gathering and analysing data. I have adopted Gilbert and Mulkay's (1984) concept of an 'interpretative repertoire' to manage the construction of discursive patterns identified in the data. Semi-structured interviews with 21 people with physical and sensory disabilities, who used the online medium daily, or several times per week, were carried out. Participants were recruited from various disability organisations in New Zealand and were invited to take part in an online interview via email, or another online communication program of their choice. Participants were met in person prior to the interviews to confirm the researcher's credibility and to build rapport.Seven key repertoires were identified in the data, with each one organised around several discursive resources. A choice to disclose repertoire allows disability to become a flexible feature of identity to be revealed and/or concealed in a contextualised and occasioned fashion. The accessing a socially valued subjectivity repertoire enables people with disabilities to position themselves as valued members of the social world, free of the physical and psychological barriers constructed by others that surround disabled identities. A transcendence repertoire functions in the talk of people with disabilities by surpassing the physical, social, and psychological limitations arising from having to operate within a disabled body, allowing far greater capacity for participation. A participating in the world repertoire affords people with disabilities the opportunity to be part of a wider community of relationships, people, interests, activities, and information, creating a sense of global belonging and connection. The keeping safe and qualified deception repertoires, together, enable people with disabilities to successfully manage the dilemma of participating in a medium where there is potential for substantial self-gain as well as harm. In contrast to the repertoires available for experiencing alternative subjectivities, which operate outside the oppression of disabled identities, a disabling differentials repertoire demonstrates the social disadvantages surrounding disabled identities online. Discursive findings are discussed in relation to disembodiment, as the online medium enables abilities to extend beyond the body, lifting the ceiling on standard ways of operating. This opens up psychological benefits as people with disabilities are afforded opportunities to access and participate within many dimensions of social life. At a collective level, political implications associated with the absence online of disabled identities are raised. Issues of technopower are also mentioned, along with future research directions. Overall, participants' constructions demonstrate how the online medium makes available a social space where people with disabilities can temporarily step outside the physical, social, and psychological constraints of operating within disabled subjectivities. This was cherished and celebrated.
Keywords: Disability; Online experience; Identity; Discourse analysis; Social psychology; Cyberpsychology; 380105 Social and community psychology